Optimization and evaluation of sirolimus nanodispersion drug-layered prednisolone tablets for the management of thrombocytopenia - Pradeep Jena; Achal Mishra; Madhuri Baghel; Mayank Garhewal; Shekhar Verma (Journal of Applied Pharmaceutical Research, 2026)
Background: Thrombocytopenia is a hematological disorder characterized by a reduced platelet count, increasing the risk of bleeding and impairing hemostasis. The present study aimed to develop and optimize a fixed-dose combination tablet comprising a sirolimus nanodispersion layered onto a prednisolone core tablet using a Box–Behnken experimental design as a potential therapeutic strategy for thrombocytopenia. Methodology: Sirolimus nanodispersion drug-layered tablets were prepared and optimized using a three-factor, three-level Box–Behnken design. The optimized formulation was evaluated for critical quality attributes, including hardness and friability, and subsequently experimentally validated. Therapeutic efficacy was investigated in cyclophosphamide-induced thrombocytopenic Wistar rats by assessing platelet count, bleeding time, clotting time, and hematological parameters, including red blood cell count, hemoglobin, and hematocrit. Results and Discussion: The optimized formulation exhibited acceptable mechanical properties, with hardness ranging from 5.3 to 5.5 kg/cm² and friability below 1%, confirming the robustness of the optimization process. In vivo evaluation demonstrated a marked improvement in platelet recovery following treatment. The platelet count increased from 39.87 ± 8.82 × 10³/mm³ in the disease control group to 132.62 ± 21.76 × 10³/mm³ and 154.57 ± 7.40 × 10³/mm³ after once-daily and twice-daily administration, respectively. Furthermore, treatment significantly improved bleeding time, clotting time, and hematological parameters, indicating enhanced therapeutic efficacy. Conclusion: The optimized sirolimus nanodispersion drug-layered prednisolone tablet demonstrated favorable pharmaceutical characteristics and significant therapeutic efficacy in the cyclophosphamide-induced thrombocytopenia model. The developed fixed-dose combination represents a promising formulation strategy for improving the management of thrombocytopenia and warrants further preclinical and clinical investigation.